Right ventricular outflow tract pacing: An alternative, safe, and effective pacing site - (:unkn) unknown (Begell House Inc., 2010)
The right ventricular apex (RVA) has traditionally been preferred for the insertion of permanent cardiac pacemaker leads because of vast experience with their use, their ease of implantation, and the stability of passive fixation leads in the RVA trabeculae. However, prolonged RVA pacing is associated with progressive left ventricular dysfunction due to dysynchronous ventricular activation, and often results in substantial functional, hemodynamic, electrical, and structural changes, as previously demonstrated in many studies. Only in recent years has interest in the use of alternate pacing sites developed. The right ventricular outflow tract (RVOT) is now the preferred site of pacing because of potential advantages such as ease of application, better hemodynamics, synchronous activation, fewer myocardial perfusion defects, and a narrower QRS complex compared with RVA pacing. This review article comprehensively discusses this novel technique in terms of its beneficial effects, long-term safety, and performance measures compared with RVA pacing, and as an alternative method for biventricular pacing. © 2010 by Begell House, Inc.
Keywords: Cardiac resynchronization; Hemodynamics; Myocardial perfusion; Pacing; Pacing site; Right ventricular outflow tract